2014
DOI: 10.2460/ajvr.75.12.1064
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of retinoids and carotenoid derivatives on caspase-3–dependent apoptosis and efferocytosis of bovine neutrophils

Abstract: Neutrophil apoptosis and subsequent efferocytosis by macrophages are key mechanisms in the resolution of inflammation. Findings for the present study indicated that all-trans retinoic acid and fully oxidized β-carotene could be novel nutraceutical strategies that may confer anti-inflammatory benefits for cattle with respiratory tract disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…Removal of β-carotene, particularly natural sources, such as alfalfa, from diets has resulted in the simultaneous, albeit unintended, removal of the naturally present β-carotene copolymers and their associated benefits. The positive effects on growth performance and health observed with OxBC in these trials coupled with similar findings in previous trials in swine (Hurnik et al, 2011; Chen et al, 2020), poultry (Kang et al, 2018) and dairy calves (Duquette et al, 2014) demonstrate that re-introduction of very low amounts of β-carotene oxygen copolymer into feeds can beneficially support the health and productivity of livestock and substantially reduce the need for in-feed antibiotics.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Removal of β-carotene, particularly natural sources, such as alfalfa, from diets has resulted in the simultaneous, albeit unintended, removal of the naturally present β-carotene copolymers and their associated benefits. The positive effects on growth performance and health observed with OxBC in these trials coupled with similar findings in previous trials in swine (Hurnik et al, 2011; Chen et al, 2020), poultry (Kang et al, 2018) and dairy calves (Duquette et al, 2014) demonstrate that re-introduction of very low amounts of β-carotene oxygen copolymer into feeds can beneficially support the health and productivity of livestock and substantially reduce the need for in-feed antibiotics.…”
Section: Discussionsupporting
confidence: 81%
“…Results from studies in an experimental model of bovine respiratory disease (BRD) and in gestating/lactating sows demonstrate an anti-inflammatory action for OxBC. In the experimental BRD trial, animals that received dietary supplementation with OxBC had a significant increase in anti-inflammatory or pro-resolution activity in the lung (Duquette et al, 2014) while OxBC-supplementation in gestating/lactating sows led to reductions in the concentration of pro-inflammatory cytokines, TNFα and IL-8 in colostrum and milk (Chen et al, 2020). Reduced inflammation may also be partly responsible for the observed reduction in intestinal lesion severity in C. perfringens-challenged broilers (Kang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The E3 ubiquitin ligase mouse double minute homolog 2 (MDM2), whose gene is transcriptionally activated by p53, can act as a direct negative regulator of NFκB by binding and inhibiting p65RelA [ 45 ]. Furthermore, ATRA-p53-induced neutrophil apoptosis may reduce inflammation in acne [ 46 – 48 ]. ATRA has also been shown to induce apoptosis and suppression of NFκB signalling in adult T cell leukaemia cells [ 49 ].…”
Section: Retinoic Acidmentioning
confidence: 99%
“…The second discovery relates to the biological activity of the compound mixture, which is termed oxidised β-carotene (OxBC). In vitro and in vivo studies demonstrated the presence of immune modulating activities for OxBC, including the ability to (1) prime the innate immune system and (2) limit the extent of inflammation (7,8) . Furthermore, the newly discovered copolymers were shown to be responsible for the innate immunological activities of OxBC, while the norisoprenoids appeared to be inert with regard to immunological activity (7) .…”
mentioning
confidence: 99%